Burn trauma from a space heater requiring paraspinal muscle flap back reconstruction with skin grafting: A case report. (December 2022) - Stuart, Katherine; Culhane, John; Brown, Dan; Mercier, Philippe; Kaswan, Sumesh; Israel, Heidi; Moran, Vicki
Abstract: Full-thickness burns damage all layers of skin and may also damage underlying tissue including bones, muscles, and tendons. Full-thickness burns almost always require immediate medical and surgical management. Some may require extensive bone, muscular, and other reconstructive surgery depending on the depth of involvement of surrounding tissues. Bone exposure in burn patients can lead to unique complications including osteomyelitis. We present the case of an elderly patient with a history of dementia who presented with full-thickness burns to the back with exposed spinal elements who later developed osteomyelitis requiring lumbar spine reconstruction with bilateral paraspinous muscle flap for back reconstruction, adjacent tissue transfer, and split thickness skin grafting. This case represents the severity of full-thickness burns with underlying bone exposure and the importance of aggressive wound care and multidisciplinary team approach.